Pelatihan Keterampilan Pembuatan Tas (Tote Bag) dari Limbah Karung Terigu untuk Menumbuhkan Minat Wirausaha bagi Para Guru SD Waskito di Pamulang (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
This community service activity aims to provide education about how to make tote bags from Wheat Sack Waste to SD Waskito’s Teachers in Yayasan Pendidikan Waskito Pamulang, Tangerang Selatan. The target of this project plan is one of the tri dharma of university is community service activity. The method used by Lecturer Team of Universitas Indraprasta PGRI in this activity begins with giving lecture about utilization of wheat sack waste that can be recycle to a new product, then continued by giving practice make the tote bag for all of SD Waskito’ teacher which amounted 20 teachers. The products will be produced in the form of tote bag made of wheat sack waste materials. This tote bag can function as a reusable shopping bag and has a selling point.